PROFESIONAL AUDITOR FORENSIK DAN KEMAMPUAN MENGUNGKAP FRAUDLENT PRACTICE SUATU ALTERNATIF LAYANAN - Muh Rum (AkMen JURNAL ILMIAH, 2016)
This study aims to predict the occurrence of fraudulent practices or fraudlent the manufacturing industry. This research was conducted in Singapore by ricochet analysis unit at the manufacturing industry with a sample of 200 people from the elements of supervisors and managers. The scale of the data used in ordinal scale Likerts. Technical analysis used by multiple linear regression model that diolh with software Smart PLS V, 2. Audit results show RiskValid enelitian and not significant, GreedValid and not significant, KeluargaValid Relations and Internal ControlValid significant and significant, and significant PengelolaValid Moral, OpportunityValid and not significant, PengungkapanValid and not significant, and Premature sign offValid and not significant